2012
DOI: 10.1186/1743-422x-9-60
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel mycovirus in the cultivated mushroom, Lentinula edodes

Abstract: BackgroundIn the 1970s, mycoviruses were identified that infected the edible mushroom Lentinula edodes (shiitake), but they were not regarded as causal agents for mushroom diseases. None of their genes has been sequenced. In this study, the dsRNA genome of a mycovirus recently found in a shiitake commercial strain was sequenced and its molecular structure was characterized.MethodsA cDNA library was constructed from a dsRNA purified from the fruiting body of L. edodes. The virus was tentatively named L. edodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 22 publications
0
25
1
1
Order By: Relevance
“…RfV1 was clustered with PgLV-1, LeV and RnMBV1 in a separate clade, independent of other genera. Previous studies have indicated that both PgLV-1 and LeV have monopartite dsRNA genomes and their genome organizations are similar to that of RfV1 [24,25,30]. We failed in preliminary attempts to purify virus particles from R. fumigata AG-Ba isolate C-314 Baishi.…”
Section: Sequence Propertiescontrasting
confidence: 52%
See 3 more Smart Citations
“…RfV1 was clustered with PgLV-1, LeV and RnMBV1 in a separate clade, independent of other genera. Previous studies have indicated that both PgLV-1 and LeV have monopartite dsRNA genomes and their genome organizations are similar to that of RfV1 [24,25,30]. We failed in preliminary attempts to purify virus particles from R. fumigata AG-Ba isolate C-314 Baishi.…”
Section: Sequence Propertiescontrasting
confidence: 52%
“…We failed in preliminary attempts to purify virus particles from R. fumigata AG-Ba isolate C-314 Baishi. Attempts to purify the virions of PgLV-1 and LeV were also unsuccessful, suggesting that they may be unencapsidated [24,25]. RnMBV1 consists of two dsRNA segments, dsRNA1 (8931 bp) and dsRNA2 (7180 bp), and is the only member of a newly approved virus family, Megabirnaviridae.…”
Section: Sequence Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…El ensamble De novo comparando con secuencias de genomas de virus disponibles en la base de datos del NCBI ha permitido identificar nuevas especies de endornavirus y micovirus (Espach et al, 2012;Jo et al, 2015;Khalifa et al, 2016). Utilizando dsRNAs virales, en combinación con secuenciación profunda, los investigadoress han podido obtener secuencias genómicas completas de fitovirus y micovirus (Al Rwahnih et al, 2011;Candresse et al, 2013;Coetzee et al, 2010;Deker y Parker, 2014;Espach et al, 2012;Quito-Avila et al, 2011;Magae, 2012), e identificar elementos que semejan virus en poblaciones microbianas acuáticas (Nerva et al, 2016). La secuenciación profunda de una sola vid reveló un viroma dominado por micovirus (Al Rwahnih et al, 2011).…”
Section: Field Surveysunclassified